Vitamin K antagonist vs direct oral anticoagulants with antiplatelet therapy in dual or triple therapy after percutaneous coronary intervention or acute coronary syndrome in atrial fibrillation: Meta‐analysis of randomized controlled trials. Issue 9 (9th July 2019) - Roule, Vincent; Ardouin, Pierre; Briet, Clément; Lemaitre, Adrien; Bignon, Mathieu; Sabatier, Rémi; Champ‐Rigot, Laure; Milliez, Paul; Blanchart, Katrien; Beygui, Farzin
Abstract: Background: The combination of vitamin K antagonists (VKA) for atrial fibrillation (AF) and antiplatelet agents following percutaneous coronary intervention (PCI) is associated with an increased bleeding risk. Hypothesis: Direct oral anticoagulants (DOAC) are associated with a greater safety profile but the optimal antithrombotic treatment strategy, especially when considering ischemic events, is unclear. Methods: We performed a meta‐analysis of randomized controlled trials comparing outcomes in AF patients following PCI and/or acute coronary syndrome (ACS) when treated with DOAC vs VKA, both in combination with one (dual) or two (triple) antiplatelet regimens. A systematic review was performed by searches of electronic databases MEDLINE (source PubMed) and the Cochrane Controlled Clinical Trials Register Database as well as Cardiology annual meetings. Three studies were finally included. Results: Compared to VKA triple therapy, the use of DOAC was associated with a decreased risk of any bleeding (relative risk [RR] 0.68 [0.62; 0.74]), major bleeding (RR 0.61 [0.51; 0.75]) and intracranial bleeding (RR 0.33 [0.17; 0.66]) and similar rates of the composite efficacy endpoint (RR 1.0 [0.87; 1.14]) and its components. Similar and consistent results were observed with both dual and triple therapy including a DOAC compared to VKA. Conclusion: Our meta‐analysis supports the use of dual therapy combining a DOAC and clopidogrel as the default regimen in most AF patients after PCI and/or ACS.